A Rare Case of Coexistence of Borderline Lepromatous Leprosy with Tuberculosis Verrucosa Cutis. (24th November 2016) - Dey, Biswajit; Gochhait, Debasis; Prabhakaran, Nagendran; Chandrashekar, Laxmisha; Behera, Biswanath
Abstract : Occurrence of pulmonary tuberculosis with leprosy is known but association of cutaneous tuberculosis with leprosy is rare. We report a case of borderline lepromatous leprosy coexistent with tuberculosis verrucosa cutis in a 29-year-old male, who presented with multiple skin coloured nodules and hyperkeratotic scaly lesions of 3-month duration. Dual infections are associated with high mortality and morbidity. Therefore early diagnosis and management helps to reduce mortality and to mitigate the effects of morbidity.